Examining the Product Quality Attributes that influences customer satisfaction most when the price was discounted: A case study in Kuching Sarawak - Jakpar, S.; Goh, S.; Johari, Anita; Myint, Khin (Centre for Promoting Ideas, 2012)
The study is about customer satisfaction towards the product quality. The effect of low pricing product with the product quality plays the same result of low price products produces low quality product and vice-versa. Data instrument that is used in obtaining data is by distributing survey questionnaire. The main purpose of this research is to classify whether the eight dimension of product quality after price discounting is satisfying towards customer. The respondent of the research was chosen through sampling method by using the non-probability sampling. The results infer that that the customer’s satisfaction towards the discounted product quality is based on the three attributes most namely perceived quality, performance and reliability. The Perceived quality- on image, brand name, and advertising is positively related to the level of satisfaction towards the quality of discounted product; were all supported as the relationships between the variables were statistically significant. This study does also provide useful guidelines for future researcher to be more rigorous and also in-depth to empirical and theoretical processes. In future study, customer satisfaction towards discounted product quality of the product to be specified to a product only determine by one gender (female) and also a perception towards a certain discounted price level of a product and its quality with extension of product design and customer requirements.